The Early Miocene Provenance Shift of ODP Site 1177 and Implications for the Tectonic Evolution of the Shikoku Basin, Philippine Sea Plate - Liu, Wei; Feng, Wanyi; Gai, Congcong; Zhou, Yang; Zhong, Yi; Cao, Wei; Li, Yuanjie; Zhao, Xixi; Liu, Qingsong (Frontiers in Earth Science, 2022)
The Ocean Drilling Program Site 1177 recovered the oldest (∼23 Ma) sedimentary records in the Shikoku Basin, northeastern part of the Philippine Sea Plate. Changes in sediment provenances bear important implications for the tectonic evolution of the Philippine Sea Plate, but existing data are still controversial for the early Miocene. By integrating Sr-Nd isotopes, rock-magnetic parameters, diffuse reflectance spectroscopy, and the previous data on the detrital zircons and clay minerals from Site 1177, we found that a significant provenance shift occurred at ∼16.5 Ma. The sediments of Site 1177 before ∼16.5 Ma were mainly sourced from the Pearl River and Izu-Bonin Arc, but changed to the Yangtze River and Izu-Bonin Arc sources after that. This provenance shift was strongly linked with the northward motion and clockwise rotation of the Shikoku Basin in the Miocene, which marked the final time of separation between the Shikoku Basin and the South China Sea.